Early Detection Tool of Intestinal Dysfunction: Impact on Necrotizing Enterocolitis Severity - Fox, Jenny R.; Thacker, Leroy R.; Hendricks-Muñoz, Karen D. (American Journal of Perinatology, 2015)
Objective The aim of this study is to determine the use of an early clinical signs and symptoms warning tool in early identification of intestinal dysfunction as a clinical strategy to decrease necrotizing enterocolitis (NEC) severity.Design Using signs and symptoms of 297 infants, of which 33 infants were diagnosed with stage II and III EC intestinal dysfunction, a five clinical category scoring tool (Neonatal Necrotizing Enterocolitis Early Detection Score [NeoNEEDS]) and strategy with abdominal X-ray alert was developed. The categories included behavior, cardiac, respiratory, gastrointestinal, and feeding tolerance. The strategy was tested in a prospective cohort of 72 infants < 1,500 g, utilizing 532 observations between 10/2012 and 9/1/2013. The statistical analysis utilized the Statistical Analysis Software (SAS).Results The earliest signs and symptoms of intestinal dysfunction (Stage I NEC) were cardiorespiratory baseline changes, p < 0.001. Abdominal distension and/or feeding intolerance were late findings associated with stage II or III NEC. Tool scores ≥ 5 predicted intestinal dysfunction (p < 0.00). Sensitivity was high (95%) with specificity of 82% and positive and negative predictive values of 76% and 95%, respectively. Use of the tool during the study period was associated with decreased NEC severity rates (Bell NEC stage II and III).Conclusion Cardiorespiratory symptoms precede gastrointestinal symptoms of intestinal dysfunction. Targeting signs and symptoms in an early warning tool to identify intestinal dysfunction can impact NEC severity progression.
Keywords: necrotizing enterocolitis; feeding intolerance; early warning system; preterm infant